Insect prophenoloxidase: the view beyond immunity - Lu, Anrui; Zhang, Qiaoli; Zhang, Jie; Yang, Bing; Wu, Kai; Xie, Wei; Luan, Yun-Xia; Ling, Erjun (Frontiers in Physiology, 2014)
Insect prophenoloxidase (PPO) is an important innate immunity protein due to its involvement in cellular and humoral defense. It belongs to a group of type-3 copper-containing proteins that occurs in almost all organisms. Insect PPO has been studied for over a century, and the PPO activation cascade is becoming clearer. The insect PPO activation pathway incorporates several important proteins, including pattern-recognition receptors (PGRP, βGRP and C-type lectins), serine proteases, and serine protease inhibitors (serpins). Due to their complexity, PPO activation mechanisms vary among insect species. Activated phenoloxidase (PO) oxidizes phenolic molecules to produce melanin around invading pathogens and wounds. The crystal structure of Manduca sexta PPO shows that a conserved amino acid, phenylalanine (F), can block the active site pocket. During activation, this blocker must be dislodged or even cleaved at the N-terminal sequence to expose the active site pockets and allow substrates to enter. Thanks to the crystal structure of M. sexta PPO, some domains and specific amino acids that affect PPO activities have been identified. Further studies of the relationship between PPO structure and enzyme activities will provide an opportunity to examine other type-3 copper proteins, and trace when and why their various physiological functions evolved. Recent researches show that insect PPO has a relationship with neuron activity, longevity, feces melanization (phytophagous insects) and development, which suggests that it is time for us to look back on insect PPO beyond the view of immunity in this review.